Usefulness and prognostic value of diagnostic tests in patients with possible chronic inflammatory demyelinating polyradiculoneuropathy. Issue 3 (22nd June 2022) - Thirouin, Jeanne; Petiot, Philippe; Antoine, Jean‐Christophe; André‐Obadia, Nathalie; Convers, Philippe; Gavoille, Antoine; Bouhour, Françoise; Rheims, Sylvain; Camdessanché, Jean‐Philippe
Abstract: Introduction/Aims: Recent guidelines define chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and possible CIDP. The aims of our study were to evaluate the value of diagnostic tests to support the diagnosis of CIDP in patients with possible CIDP and to identify prognostic factors of therapeutic success. Methods: We conducted an observational retrospective two‐center study between 2014 and 2019. We selected patients with a clinical presentation suggesting CIDP, but whose electrodiagnostic (EDX) test results did not meet the EFNS/PNS 2021 criteria. We analyzed epidemiologic and clinical features, axonal loss on EDX, cerebrospinal fluid (CSF), somatosensory evoked potentials (SSEPs), plexus magnetic resonance imaging (MRI), nerve biopsy, and therapeutic response. Results: We selected 75 patients, among whom 30 (40%) responded to treatment. The positivity rates of CSF analysis, MRI and SSEPs were not influenced by the clinical presentation or by the delay between symptom onset and medical assessment. A high protein level in CSF, female gender, and a relapsing–remitting course predicted the therapeutic response. Discussion: It is important to properly diagnose suspected CIDP not meeting EFNS/PNS 2021 EDX criteria by using supportive criteria. Specific epidemiological factors and a raised CSF protein level predict a response to treatment. Further prospective studies are needed to improve diagnosis and the prognostic value of diagnostic tests in CIDP.